2017
DOI: 10.1371/journal.pone.0180512
|View full text |Cite
|
Sign up to set email alerts
|

Non-skeletal health effects of vitamin D supplementation: A systematic review on findings from meta-analyses summarizing trial data

Abstract: BackgroundA large number of observational studies have reported harmful effects of low 25-hydroxyvitamin D (25OHD) levels on non-skeletal outcomes. We performed a systematic quantitative review on characteristics of randomized clinical trials (RCTs) included in meta-analyses (MAs) on non-skeletal effects of vitamin D supplementation.Methods and findingsWe identified systematic reviews (SR) reporting summary data in terms of MAs of RCTs on selected non-skeletal outcomes. For each outcome, we summarized the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(171 citation statements)
references
References 307 publications
6
154
0
9
Order By: Relevance
“…Observational studies report an association between low blood concentrations of 25-hydroxyvitamin D (the major vitamin D metabolite) and susceptibility to acute respiratory tract infections [29,30]. Consistent with these findings, several recent meta-analyses have concluded that vitamin D supplementation can reduce the risk of respiratory tract infections in both children and adults [11,[31][32][33][34][35]. In 2017, Martineau and colleagues performed a systematic review and meta-analysis of individual participant data (n = 10,933) from 25 randomized, double blind, placebo controlled trials of vitamin D supplementation with a specified outcome of acute respiratory tract infection (ARI).…”
Section: Nutritional Impact On Immunitymentioning
confidence: 78%
“…Observational studies report an association between low blood concentrations of 25-hydroxyvitamin D (the major vitamin D metabolite) and susceptibility to acute respiratory tract infections [29,30]. Consistent with these findings, several recent meta-analyses have concluded that vitamin D supplementation can reduce the risk of respiratory tract infections in both children and adults [11,[31][32][33][34][35]. In 2017, Martineau and colleagues performed a systematic review and meta-analysis of individual participant data (n = 10,933) from 25 randomized, double blind, placebo controlled trials of vitamin D supplementation with a specified outcome of acute respiratory tract infection (ARI).…”
Section: Nutritional Impact On Immunitymentioning
confidence: 78%
“…RCTs comparing outcomes for participants treated or given a placebo are preferred to establish causality related to health outcomes. However, most vitamin D RCTs have not reported that vitamin D supplementation reduced the risk of disease [62,63]. Reasons for the lack of agreement between observational studies and RCTs seems to be due to several factors, including enrolling participants with relatively high 25(OH)D concentrations and using low vitamin D doses and not measuring baseline and achieved 25(OH)D concentrations.…”
Section: Clinical and Epidemiological Findings Regarding Covid-19mentioning
confidence: 99%
“…A subsequent trial analysis, systematic review and meta-analysis suggest that vitamin D supplementation might protect against fatal and non-fatal CHFs in older, healthy people (HR 0.75, 95% CI 0.58-0.97), but not against MI or stroke [48]. The most recent meta-analysis on non-skeletal effects of vitamin D supplementation demonstrates that most trials have been done in subjects without low 25[OH]D levels limiting the credibility of the argument that vitamin D supplementation has no potential benefit on outcomes in people with 25[OH] D insufficiency [1]. The Vitamin D Assessment study (ViDA) in 5100 healthy subjects, aged > 50 years, recently reported that 100,000 IU oral vitamin D 3 monthly was neutral for the prevention of CV disease [49,50], with a low rate of 25[OH]D deficiency in participants (25%), a lower than expected endpoint rate and monthly doses cited as possible reasons [51].…”
Section: Vitamin D As An Interventionmentioning
confidence: 99%
“…Low serum 25-hydroxyvitamin D (25[OH]D) concentrations have been associated with an increased risk of adverse outcomes generally, [1,2] but especially in patients with suspected coronary artery disease, hypertension and chronic heart failure (CHF) [3][4][5][6][7][8][9][10]. However, published data pertaining to CHF are derived from registry data, or somewhat selected cohorts such as patients referred for coronary angiography, on a waiting list for cardiac transplantation or in-patients.…”
Section: Introductionmentioning
confidence: 99%